Sadomasochism Behavior in the Family According to Law Number 23 Of 2004 Concerning the Elimination of Domestic Violence (PKDRT) - Iqbal Maulana (Rechtsvinding, 2024)
This study aims to provide a comprehensive understanding of Domestic Violence (DV), particularly related to sadomasochistic behavior, through the perspectives of positive law and Islamic law. The study examines Law Number 23 of 2004 on the Elimination of Domestic Violence (PKDRT), covering its concepts, scope, and implementation in protecting victims, as well as analyzing the resolution of DV cases involving individuals with sadomasochistic tendencies according to Islamic law and its relevance to PKDRT. The research employs a qualitative approach using library research, relying on secondary data from primary legal sources, secondary legal literature, and non-legal sources, including psychology, sociology, and health literature related to violence and sexual deviations. Data collection was conducted through literature review, followed by data processing in stages of editing, organizing, and analyzing. Data analysis was carried out descriptively and analytically using a deductive method, from general concepts of sexual deviation to specific DV cases arising from sadomasochism. The findings indicate that from the perspective of fikih munakahat, sadomasochistic behavior causing violence to one party is not permissible; conflict resolution should prioritize persuasive and non-violent approaches, while punishments for perpetrators are clearly regulated, including flogging, imprisonment, diyat, qisas, and penalties for defamation, aiming to protect victims and prevent repeated violence. From the perspective of Law No. 23/2004, the government plays a strategic role in prevention and handling of DV through policy-making, education, socialization, gender-sensitive training, provision of specialized services, professional staff, and protection for victims and their companions.